Pengaruh Media Boneka Jari Kertas Terhadap Keterampilan Berbicara Di Kelas Rendah - Ratna Sari Elisa; Astri Sutisnawati; Iis Nurasiah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
The research aims to determine the effect of paper finger puppet learnt media on speaking skills in low class. The type of research used in this study is Quasi Experimental Design with the design of Nonquivalent Control Group Design. The sample of this research was class IIIA and Class IIIB Baros Kencana Elementary School CBM Sukabumi City. Data collection was carried out by a test method consisted of pretest and posttest. Learnt conducted in the experimental class uses paper finger puppet learnt media, while the learnt done in the control class does not use media. The calculation results show the experimental class has a higher average value of learnt outcomes compared to the control class. The average final grade of the experimental class is 79 while the control class is 63. In addition, the results of tested from the t-test of two independent samples show the results of sig. equal to 0,000 which means that the value is less than 0.05. So it can be concluded that there is a significant influence on the use of paper finger puppets on the speaking skills of students in the low class.